Phenomenology as First Philosophy and Metaphysics. Some Thoughts on Husserl’s Method and System - Luft, Sebastian (Bollettino Filosofico, 2024)
In this article, I shall address some of the central points tied to his claim that phenomenology should come forth as “first philosophy”. Understanding these can help the reader understand the main intentions driving Husserl. But before that, I will start out with a simple definition of what phenomenology is; this will provide the basis for my discussion of Husserl’s attempt to bring phenomenology forth as first philosophy. Keywords: Husserl, First Philosophy, Descartes, Aristoteles, Phenomenology, Transcendental Philosophy